2016
DOI: 10.5114/pg.2015.55700
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic importance of faecal markers in long-term monitoring of anti-TNF- therapy in primary responders with Crohn’s disease

Abstract: IntroductionMonitoring the response to biological treatment in Crohn’s disease (CD) is a very important element of the therapeutic optimisation.AimTo evaluate the usefulness of measuring calprotectin, lactoferrin, and myeloperoxidase in stool as markers of long-term clinical and endoscopic response to anti-tumour necrosis factor α (anti-TNF) treatment in CD.Material and methodsThe studied group consisted of 35 CD patients treated with anti-TNF-α antibodies. Clinical activity was evaluated using Crohn’s Disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Repeated measurement of FC indicates that a drop of pretreatment stool concentration is effective in predicting response to anti‐tumor necrosis factor‐α antibodies. Again, differing reduction values versus baseline were used for predicting favorable responses (Table ) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Repeated measurement of FC indicates that a drop of pretreatment stool concentration is effective in predicting response to anti‐tumor necrosis factor‐α antibodies. Again, differing reduction values versus baseline were used for predicting favorable responses (Table ) …”
Section: Resultsmentioning
confidence: 99%
“…Again, differing reduction values versus baseline were used for predicting favorable responses (Table 4). [36][37][38][39][40][41][42][43][44] Conversely, minor reductions of FC (< 70%) after anti-tumor necrosis factor-α antibodies induction predict non-response. 42 14 50 μg/g 59 71 --P = 0.008 Sipponen 2012 29 14 100 μg/g 36 89 --P = 0.008 Höög 2014 26 30 ---Lewis score Inclusion r = 0.54 Inclusion P = 0.003 Höög 2014 26 30 ---Lewis score Follow-up r = 0.83 Follow-up P < 0.001 Egea-Valenzuela 2015 25 68 50 μg/g 96 23 Lewis score r 2 = 0.1 -Egea-Valenzuela 2015 25 34 100 μg/g 75 67…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This biomarker may be adapted in biolog ical therapy monitoring, which is nowadays com monly used in IBD care in Poland. [21][22][23] It has been shown that FC elevation predicts short term re lapse after discontinuation of antitumor necrosis factor α therapy in patients with IBD in deep re mission. 24 Moreover, in the POCER study, Wright et al 25 found that FC elevation predicted early postoperative recurrence in patients with CD.…”
mentioning
confidence: 99%